EFFICIENT REMOVAL OF BASIC YELLOW 51 DYE VIA CARBONIZED PAPER MILL SLUDGE USING SULFURIC ACID - Yaras, Ali; Arslanoglu, Hasan (Yildiz Technical Univ, 2018)
In present study, paper mill sludge (PMS) in cellulosic structure carbonized with sulfuric acid was utilized for adsorption of cationic basic yellow 51 (BY 51) dye from synthetic solution. The parameters affecting on removal of BY 51 dye following; initial pH (2-11), amount of carbonized paper mill sludge (CPMS) (0.25-1.5 g/l), initial concentration (0.5-2 mM), time (0-360 min.) and temperature (25-55 degrees C) were studied in the batch adsorption experiments. The physical and chemical properties of prepared CPMS were determined using elemental analyzes, scanning electron microscopy (SEM) and BET techniques. Optimum initial pH was measured to be 7 for the removal of BY 51 dye. The obtained equilibrium data in various initial concentrations of BY 51 dye solution varied from 0.5 to 2.5 mM for three temperatures (25 degrees C, 40 degrees C and 55 degrees C) were applied to Langmuir and Freundlich isotherms. The calculated maximum adsorption capacity (q(max)) from Langmuir equation was achieved 1089.45 mg/g depending on increasing temperature from 25 degrees C to 55 degrees C. The experimental results for all temperatures were applied to pseudo-first order kinetic model, pseudo-second order kinetic model and intra-particle diffusion model. Consequently, it was good agreement with the second-order kinetic model and the activation energy (E-a) is calculated as 11.642 kJ/mol. Based on the calculated thermodynamic parameters, enthalpy (Delta H degrees, + 19.32 kJ/mol), free energy (Delta G degrees, -23.02 kJ/mol) and entropy (Delta S degrees, 0.142 kJ/molK). The results showed that the adsorption phenomena of cationic BY 51 dye is of endothermic and spontaneous nature. The findings presented that CPMS could be utilized as adsorbent in the treatment of industrial wastewater.
Keywords: Paper mill sludge; basic yellow 51; carbonization; adsorption; isotherm; kinetic